SYARAT-SYARAT PEMBENTUKAN PERJANJIAN WARALABA BERDASARKAN PERATURAN PEMERINTAH NOMOR 42 TAHUN 2007 TENTANG WARALABA - Elrian Angelita, Zhanniza; Tjatrayasa, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015, 2015)
The background of writing the paper which entitled Terms of Establishment of Franchisee Agreement Based on Government Regulation Number 42 of 2007 on Franchising is the importance to acknowledge the terms that must be fulfilled in drafting the franchisee agreement, so it is able to protect the interests of the franchisor and the franchisee. The method used in this paper is normative method by analyzing Government Regulation Number 42 of 2007 on Franchising and various literatures related to franchise agreement drafting. Franchises agreement contains a set of terms, conditions and commitments, drafted and desired by the franchisor to its franchisee. In the franchisee agreement there are two parties involved, namely, the franchisor as a party who has the system or way of doing business, and franchisee as a party that bought the franchisee or the franchises system’s franchisor so that it has the right to conduct business in the way that developed by the franchisor. The conclusion of this paper is the establishment of a franchise agreement must fulfilled the terms of the franchise agreement as stipulated in Article 4, 5, and 6 of Government Regulation Number 42 of 2007 on Franchisee to protect the interests of the franchisor and the franchisee.
Keywords: Franchising, Franchisor, Franchisee, Terms